2003
DOI: 10.1021/ol0356284
|View full text |Cite
|
Sign up to set email alerts
|

Hydrovinylation of Norbornene. Ligand-Dependent Selectivity and Asymmetric Variations

Abstract: [reaction: see text] Norbornene undergoes Ni-catalyzed (1-2 mol% allylnickel bromide/phosphine/NaBARF or AgSbF(6), 1 bar ethylene, -50 degrees C) hydrovinylation (>97% yield), giving either a 1:1 or a 2:1 (norbornene/ethylene) adduct depending on the size of the phosphine. Use of binaphthol-derived phosphoramidite ligand results in up to 80% ee for the 1:1 adduct. The course of the reaction is highly dependent on the ligand (size and configuration of the appendages) and the counteranion present.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1
1

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 16 publications
2
33
1
1
Order By: Relevance
“…Interestingly, an h 2 interaction between ligand 1a and the metal has been predicted by calculation for nickel hydrovinylation catalysts, in which it stabilizes the hydride alkene intermediate [NiH(styrene)(1,2-h-1a-kP)] [35]. Our results may help explain the remarkable influence of the formal secondary-amine appendage (N-substituent) observed in the same reaction [36]. An analogous interaction involving a binaphthalene group has been claimed for cationic (monophosphine)palladium(II) complexes [37] [38], but it is still controversial whether the coordination mode is h 2 or h 1 [39].…”
Section: A C H T U N G T R E N N U N G (P)]supporting
confidence: 70%
“…Interestingly, an h 2 interaction between ligand 1a and the metal has been predicted by calculation for nickel hydrovinylation catalysts, in which it stabilizes the hydride alkene intermediate [NiH(styrene)(1,2-h-1a-kP)] [35]. Our results may help explain the remarkable influence of the formal secondary-amine appendage (N-substituent) observed in the same reaction [36]. An analogous interaction involving a binaphthalene group has been claimed for cationic (monophosphine)palladium(II) complexes [37] [38], but it is still controversial whether the coordination mode is h 2 or h 1 [39].…”
Section: A C H T U N G T R E N N U N G (P)]supporting
confidence: 70%
“…[375,376] Das beschriebene Screening von Phosphoramidit-Liganden resultierte zwar nicht in einer höheren Enantioselektivität, dafür verlief diese spezielle katalytische Hydrovinylierung hoch selektiv und ergab je nach Additiv das einfache Hydrovinylierungsprodukt 250 oder das hydrovinylierte Norbornendimer 248. So wurde mit AgSbF 6 als Additiv das Produkt 248 mit niedrigem ee-Wert erhalten, mit NaBArF dagegen entstand selektiv 250 mit bis zu 80 % ee.…”
Section: Phosphoramidit-ligandenunclassified
“…NaBArF, [20] phosphoramidite (R a ,S C ,S C )-5, [21] [η 3 -(allyl)NiCl] 2 , [22] and [η 3 -(allyl)Ni{(R a ,S C ,S C )-5}Cl] (6) [5a] were prepared according to literature procedures. UV/ Vis spectra were recorded with an Avantes Ava-light DHS.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we showed that phosphoramidites are extremely efficient chiral ligands for this transformation, [5] and they have gained increasing attention owing to their large substrate scope. [6,7] Scheme 1. General asymmetric hydrovinylation reaction.…”
Section: Introductionmentioning
confidence: 99%